Content Analysis of International Standards for Human Factors in Ship Design and Operation - Ibrahim, Farizha; Razali, Mohd Norsyarizad; Abidin, Noh Zainal (Transactions on Maritime Science, 2021)
Human-related factors account for more than 80% of accidents at sea, based on studies. According to Global Claims Review 2017 released by Allianz Global Corporate & Specialty, an estimated 75-96% of shipping accidents have a high probability of involving human error (AGCS, 2017). Designs that do not meet human factors' needs play a significant role in contributing to human error. Documents in terms of design standards and guidelines, rules, and laws are analyzed. As a result, several documents related to human factors have been identified. These documents are based on whether to implement it, even if some are prescriptive, and others are mandatory, being published at different enforcement levels. In ensuring the consistent implementation of human factors, regulators and authorities need to take stricter measures in all the processes involved in designing and building such ships.